Saber popular e escolarização: uma junção necessária no semiárido paraibano - Martins, Izabel Cristina (2009)
The process of education of subjects - children, youth and adults living in rural areas of the municipalities located in semi-arid of Paraiba is wrapped in a context of natural difficulties, social and economic. However, the people know it stands in overcoming the problems faced by the population. The investigations were in the rural municipality of São José de Piranhas - PB at microregion backlands paraibano with a group of individuals composed of participating farmers / residents in the area. In semi-structured interviews and informal conversations, the contents of the diary transcribed speech enabled understanding of the process of exclusion from school in which they emerged and understanding of the continuity of the educational process and the importance of knowledge in these popular courses. Analysis of data indicate the existence of the educational gap in the rural area of the semi-arid, which is related to many different and varied aspects including the failure of proposals and educational actions directed to the area. The process of education of many individuals who now live in rural areas is related to the uncertainties of starting, continuing and further education with a thriving career in search of a future professional achievement, or have a guaranteed right skills and professional skills. The investigative work subject to the semi-arid of Paraiba possible to verify the knowledge / education to learn the popular and the community, with much more effective analytical potential as greater concerns of managers and public educational institutions with the education of these subjects.